Algoritmo de Dimensionamiento de Almacenes para Obras de Edificación del Sector de la Construcción - Hualpa Zuñiga, Andres Mauricio; López Bello, Cesar Amílcar (Ingeniería, 2015)
This article contains the development of an algorithm applied to the solution of problems of sizing of storage spaces in companies in the construction sector. This problem is justified under the degree of informality that occurs at the time of assigning storage areas, without considering parameters related to stages of construction, the characteristics of the product and the provisions of the work area. In a previous study it is identified that the degree of informality at the moment of assigning storage areas, generates poor rates of capacity utilization and delivery of incomplete orders. The design of the algorithm is supported by a comprehensive model of sizing subjected to a system of equations with variables of quantity, volume and material dimensions, to finally establish the necessary storage area. The algorithm is adapted to programming language in order to present the results in graphic language where the sizing of storage spaces is visible. These results are validated through the evaluation of storage capacity utilization and completely delivered orders for different cargo units, where improvements in these indicators are shown.